Development of Ammonia-Salts Adsorption Working Pairs in Chemical Heat Pump - 马刚; 李戬洪; 马伟斌; 梅建滨 (Zhileng xuebao)
Adsorption working pairs of ammonia-salts in chemical heat pump was analyzed and summarized. On the basis of the various heat sources, feasible adsorption working pairs were founded. The adsorption mechanism was analyzed and the application foreground of heat pump was discussed.